Bimetallic Cu-Ni/TiO2 as photocatalyst for hydrogen production from water - Nurlaela, Ela; Chong, Fai Kait; Dutta, Binay Kanti; Riaz, Nadia (2010)

(untitled)
A series of titania-supported copper-nickel bimetallic photocatalysts (Cu-Ni/TiO2) were prepared and studied. The photocatalysts were synthesized by precipitation method. The raw photocatalysts were calcined at three temperatures: 180, 200 and 250°C for different duration (0.5, 1, and 2 hours). The physical and chemical properties of the catalysts were investigated using thermogravimetric analysis (TGA), Fourier Transform Infrared spectroscopy (FTIR), diffuse reflectance UV–Vis spectroscopy (DR UV-Vis), powder X-ray diffraction (XRD) and field-emission Scanning Electron microscopy (FESEM). The photocatalytic activities of the catalysts were studied for solar hydrogen production from water under visible light illumination. The results indicated that deposition of copper and nickel onto TiO2 enhanced the activity of the photocatalysts compared to bare TiO2. Bimetallic photocatalyst calcined at 200°C for 1 h produced the highest amount of H2 (5.0 mL) similar to that produced by monometallic Cu/TiO2. The addition of a second metal enhanced the performance of Ni/TiO2 but not Cu/TiO2. Details of the synthesis procedure, catalysts characterization, and photocatalytic studies are presented in this paper.